Analisis Hustle Culture Terhadap Work Life Balance pada Pekerja Remote di Kota Denpasar - Revy Aurlia Adistya; Anom Kumbara; Ida Ayu Alit Laksmiwati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The rise of remote work is increasingly popular among Generation Z workers in Denpasar, Bali, especially in creative and technical fields. This study analyzes the factors driving the emergence of hustle culture and its impact on work-life balance. Using qualitative and ethnographic methods, data was collected through observation, interviews, and literature review. The findings show that easy access to technology, flexible work patterns, and performance-oriented company culture are key drivers of hustle culture. While this culture enhances creativity, it blurs the line between work and personal life, leading to stress and reduced well-being. The study also reveals how the unique cultural and social context in Denpasar influences this phenomenon. These insights provide guidance for workers and organizations to create a better work-life balance.